QUOTIENT SEMINEAR-RINGS OF THE ENDOMORPHISM OF SEMINEAR-RINGS - Fatimah, Meryta Febrilian; Hasnani, Fitriana; Puspita, Nikken Prima (PATTIMURA UNIVERSITY, 2022)
A seminear-ring is a generalization of ring. In ring theory, if is a ring with the multiplicative identity, then the endomorphism module is isomorphic to . Let be a seminear-ring. Here, we can construct the set of endomorphism from to itself denoted by . We show that if is a seminear-ring, then is also a seminear-ring over addition and composition function. We will apply the congruence relation to get the quotient seminear-ring endomorphism. Furthermore, we show the relation between c-ideal and congruence relations. So, we can construct the quotient seminear-ring endomorphism with a c-ideal.